A análise combinatória e seu ensino - Miotto, Eder (2014)
The present work has two major goals. The first one is related to the teaching of combinatorics in elementary school and high school. The second one is to seek further knowledge related to combinatorial concepts. Regarding the first goal, the teaching of combinatorics, in my trajectory as a teacher, has been one of the most arduous tasks that the math teacher of basic education faces. Therefore, some questions arise. Why a subject fully applicable to everyday, has generated so much trouble understanding? One of the goals of this work is to seek answers to this question and propose suggestions that can improve the understanding of this concept. As a second proposed goal, I sought to understand concepts that hitherto were not dominated, deepening my combinatorial knowledge. Therefore, this work has section devoted to the study of more complex combinatory concepts, not addressed to the students of high school but they allow us to understand more complex combinatorial situations.